2015
DOI: 10.1007/s12033-015-9859-0
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Bacillus subtilis Spores Elicit Th1/Th17-Polarized Immune Response in a Murine Model of Helicobacter pylori Vaccination

Abstract: Current progress in research on vaccines against Helicobacter pylori emphasizes the significance of eliciting the Th1/Th17-polarized immune response. Such polarization can be achieved by selection of appropriate antigen and adjuvant. In this study, we wanted to check the polarization of the immune response elicited by UreB protein of Helicobacter acinonychis delivered by recombinant Bacillus subtilis spores upon oral immunization. B. subtilis spores presenting fragment of UreB protein and able to express entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
(44 reference statements)
1
15
0
Order By: Relevance
“…FliD-presenting spores of the wild type strain led to bias of the response towards Th1 and Th17. Such polarization has also been observed in our previous studies involving use of recombinant spores presenting FliD fragment [ 27 , 28 ]. Lack of IL-6 (data not shown), a cytokine characteristic for Th17 polarization of the immune response, seems to result from technical problems in detecting this cytokine with the method used in our study.…”
Section: Discussionsupporting
confidence: 82%
“…FliD-presenting spores of the wild type strain led to bias of the response towards Th1 and Th17. Such polarization has also been observed in our previous studies involving use of recombinant spores presenting FliD fragment [ 27 , 28 ]. Lack of IL-6 (data not shown), a cytokine characteristic for Th17 polarization of the immune response, seems to result from technical problems in detecting this cytokine with the method used in our study.…”
Section: Discussionsupporting
confidence: 82%
“…To check how the choice of anchoring protein influences interaction of the recombinant spores with the immune system, we performed mucosal immunization of mice with all variants of the FliD-presenting spores. Since results of our previous research indicated that the recombinant spores did not elicit immune response in mice upon oral immunization without the use of appropriate adjuvants (Hinc et al, 2014;Stasiłojć et al, 2015), we decided to administrate spores by the intranasal route, which was shown to be compatible with such antigen delivery systems (Huang et al, 2010;. We were not able to detect a statistically significant increase in levels of FliD-specific antibodies in sera, lungs or gastrointestinal tracts of immunized animals (data not shown).…”
Section: Immune Response To Recombinant Sporesmentioning
confidence: 91%
“…Oral administration of Bacillus subtilis spores expressing the UreB protein of H. acinonychis resulted in a Th1 and Th17 polarization. 16 This specific cellular immune response has been associated with protection against H. pylori infections. 17,18 Administration of a H. pylori urease-based subunit vaccine resulted in a reduction of H. felis colonization in mice.…”
Section: Treatment and Prevention Of Nhph Infectionsmentioning
confidence: 99%